Digital library: Lecturers’ perceptions of facilitating learning resources in the industrial era 4.0 - Aliyyah, Rusi Rusmiati; Rasmitadila; Fauziah, Siti Pupu; Widyasari; Marini, Arita; Ruhimat (Journal of Education and e-Learning Research, 2024)
This research explores lecturers’ perceptions of digital libraries as a learning resource for the industrial era 4.0 that can be used anytime and anywhere to solve the low interest in developing lecturers because of the difficulty of accessing references to conventional libraries, which require lecturers to visit the library building. Data was collected through semi-structured interviews with 15 lecturers, and data analysis was performed using thematic analysis. The analysis results found four main themes: benefits, challenges, recommendations, and positive and negative impacts of digital libraries. The research concluded that the existence of a digital library can make it easy for lecturers to browse the references needed quickly, easily, and flexibly just by entering the library’s website page. This research contributes to solving the problem of lecturers in Indonesia over the limited learning resources in conventional libraries that are difficult to access online and require particular visiting time because they have to come directly during library operating hours. Therefore, support from the government, university leaders, and the wider community is needed to develop a digital library system to facilitate lecturers in Indonesia having adequate learning resources for the industrial era 4.0.